Retrofitting of a historic public building for energy efficiency: exploring measurements and attitudes for heritage conservation professionals - Miran, Fenk D. (Penerbit Universiti Kebangsaan Malaysia, 2020)
During the last few decades, there has been a trend toward enhancing energy performance and improving indoor comfort conditions of heritage buildings. Architectural heritage and aesthetic values do not allow typical retrofit interventions. Governmental and planning directives mainly focus on saving energy in existing buildings and do not extend to historic buildings. Architectural heritage bodies must act to determine energy retrofit measure types that can be applied to historic buildings to conserve their values. There is a need to enhance the energy efficiency and environmental sustainability of historic buildings. This study aims to reduce a heritage building's energy use through technical interventions and selection of specific retrofit measures. Each of these interventions is then evaluated using sustainable tools. Designing energy retrofits for existing buildings has environmental, economic, social, and health benefits. This study describes a methodology for adopting Integrated Environmental Solutions–Virtual Environment (IES–VE) tools as energy and environmentally conscious decision-making aids. A methodology was developed to monitor buildings for potential improvements and support the retrofit strategy development. We present a case study of a banquet hall renovation project titled “The Banqueting Hall in Jesmond Dene, Newcastle Upon Tyne” that implements IES–VE approaches to energy retrofits to a historic public building. To generate energy savings, several improvements were added to the building. For each alteration, building energy consumption and mean radiant temperature were examined, and the results indicate that with all improvements applied to the building there is a potential to reduce total energy system demand by 45%. Restoration of historic buildings is of paramount interest for preserving a locality's character and history. Environment-friendly retrofitting helps reduce the footprint of old energy-inefficient structures. Simulations of various energy-efficient retrofitting methods are of paramount interest for planners to decide optimal strategies for improving building performance. Although several articles have been published in this area, each new building comes with unique challenges and is therefore unique and highly significant.